STEM EDUCATION :INNOVATION EDUCATION FOR YOUNG GENERATION IN ASEAN - Atchara Purakom; Theerasak Soykeree (Proceedings Education and Language International Conference, 2017)
Innovation is the process of making lives better. Whether it is a small improvement for one person or a breakthrough for society. On the largest scale, an innovation creates a shift that affects many aspects of our way of live. Shifts created by the introduction and adoption of railroads, cars, airplanes, radios, televisions, computers and the Internet, etc. have altered the way we travel, communicate, live, learn and think. To date and tomorrow’s knowledge economy, The goal of getting an education isn’t to solve some of yesterday’s problems, but to tackle problems in the future that we don’t know about today, so that students will need to be self-starters who are persistent and have an appetite for measured risk-taking. They will have to think for themselves and possess specialized or technical knowledge to thrive.STEM is a curriculum based on the idea of educating students in four specific disciplines; science, technology, engineering and mathematics. It is an interdisciplinary and applied approach rather than teach the four disciplines as separate and discrete subjects, STEM would integrate them into a cohesive learning paradigm based on real world applications. The purpose of this paper is to understand how to improve learning for new generation in ASEAN by STEM education. In a meaningful way, we are starting to see the dawn of incredible innovation in teaching and learning in ASEAN. Finally, STEM has impacted in education both in building our knowledge and skills as well as our understanding towards one another.Keywords: STEM education, Innovation Education, young generation